2D ANIMATION VIDEO AS INFORMATION ABOUT HEALTHY LIFESTYLES USING MOTION GRAPHIC TECHNIQUES - Deli Deli; Rino Rino (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Healthy lifestyle is something that everyone needs to pay attention to, because a healthy lifestyle is important to maintain a healthy body. But unfortunately, not everyone has implemented a healthy lifestyle. This is due to several reasons, such as lazy to eat healthy food because it is considered ineffective, and lack of knowledge about how to implement the right healthy lifestyle. Therefore, the author wants to design a 2D animation video about the importance of a healthy lifestyle, the animation video will be made as clear and attractive as possible, so that the video is interesting to watch and the message in the video can also be easily understood by the public. In designing this 2D animation video, the author uses several software such as, Adobe Illustrator 2019, Adobe After Effects 2020, and Adobe Premiere Pro 2020. The final result of this research is an information media in the form of 2D animation video that informs the importance of a healthy lifestyle, which was developed using the MDLC method and has a duration of 2 minutes and 10 seconds. This 2D animation video is distributed to the public through the Youtube platform, so that the animation video can be easily watched by the public. With this 2D animation video, it is hoped that it can provide information and also motivate the public to be able to implement a healthy lifestyle.